Transcranial magnetic stimulation as an antioxidant. (3rd April 2018) - Medina-Fernández, Francisco J.; Escribano, Begoña M.; Padilla-del-Campo, Carmen; Drucker-Colín, René; Pascual-Leone, Álvaro; Túnez, Isaac
Abstract: In the last decades, different transcranial magnetic stimulation protocols have been developed as a therapeutic tool against neurodegenerative and psychiatric diseases, although the biochemical, molecular and cellular mechanisms underlying these effects are not well known. Recent data show that those magnetic stimulation protocols showing beneficial effects could trigger an anti-oxidant action that would favour, at least partially, their therapeutic effect. We have aimed to review the molecular effects related to oxidative damage induced by this therapeutic strategy, as well as from them addressing a broader definition of the anti-oxidant concept.